The state of privatisation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Natural Resource Management and Institutional Change By D Carney and J Farrington. 1998. 120 pp. ISBN 0-415-18604-8 £ 40.00 Routledge 11 New Ferrer Lane London EC4P 4EE, UK